Technoeconomical investigation of energy harvesting from MIDREX® process waste heat using Kalina cycle in direct reduction iron process. (15th January 2022) - Salemi, Sina; Torabi, Morteza; Haghparast, Arash Kashani
Abstract: Iron and steel industry is one of the main energy and water consumer globally which produces high amount of waste heat and air pollution. Numerous regulations, agreements and commitments ask the industry to reduce its energy and water consumption further to its environment fingerprints. MIDREX process is one of the leading technology for direct reduction of iron oxide to sponge iron which is dominant in Iran industry with annual capacity of more than 21 million metric tons. So, recovery of waste heat is essential for this industry. In this regard, using Kalina cycle as an efficient method is investigated in terms of thermodynamic study and economically. The results for analysis of a conventional MIDREX plant in Iran with capacity of annual 1.38 Mt of sponge iron shows that more than 2 MW electricity is extractable via Kalina cycle with mixture of ammonia and water. It also reveals that the heat exchanger and condenser are the main causes of exergy destruction of the proposed system with amount of 70%. The sensitivity analysis demonstrates that concentration and pressure at evaporator affect the energy and exergy efficiencies of the system. Changing the flue gas temperature also can be controlled by changing the concentration of the mixture to keep the stability of the net power. The economic investigations represent the long term for payback period for more than 17 years based on the present feed-in-tariff prices for waste heat recovery. For making the proposed system more profitable, technical and policy modifications are considered simultaneously which is associated with payback period of less than 9 years. Highlights: Proposing of Kalina Cycle for waste heat recovery in direct reduction of iron. Energy and exergy investigation of the system to find the optimum conditions. Economic analysis of system for a 1.38 Mt sponge iron plant in Iran. Modifying the process and economical values for lowering the costs. Proposing of scenarios to promote waste heat recovery in iron plants in Iran.